Menu Close

Solve-x-x-1-2-x-x-1-2-6-




Question Number 217911 by Rasheed.Sindhi last updated on 23/Mar/25
Solve  ((x/(x−1)))^2 +((x/(x+1)))^2 =6
Solve(xx1)2+(xx+1)2=6
Answered by Rasheed.Sindhi last updated on 23/Mar/25
((x/(x−1)))^2 +((x/(x+1)))^2 =6  ((x/(x−1)))^2 −1+((x/(x+1)))^2 −1=4  ((x/(x−1))−1)((x/(x−1))+1)+((x/(x+1))−1)((x/(x+1))+1)=4  (1/(x−1))∙((2x−1)/(x−1))+((−1)/(x+1))∙((2x+1)/(x+1))=4  (((2x−1)(x+1)^2 −(2x+1)(x−1)^2 )/((x^2 −1)^2 ))=4  (2x−1)(x^2 +2x+1)−(2x+1)(x^2 −2x+1)=4(x^4 −2x^2 +1)  ▶2x^3 +4x^2 +2x−x^2 −2x−1     −2x^3 +4x^2 −2x−x^2 +2x−1       =4x^4 −8x^2 +4  ▶3x^2 −1         +3x^2 −1       =4x^4 −8x^2 +4  ▶6x^2 −2=4x^4 −8x^2 +4  ▶ 4x^4 −14x^2 +6=0  ▶2x^4 −7x^2 +3=0  ▶2x^4 −6x^2 −x^2 +3=0  ▶2x^2 (x^2 −3)−(x^2 −3)  ▶(x^2 −3)(2x^2 −1)  ▶x=±(√3) ∨ x=±(1/( (√2)))=((±(√2) )/2)  ▶x∈{(√3) ,−(√3) , ((√2)/2) ,−((√2)/2)}
(xx1)2+(xx+1)2=6(xx1)21+(xx+1)21=4(xx11)(xx1+1)+(xx+11)(xx+1+1)=41x12x1x1+1x+12x+1x+1=4(2x1)(x+1)2(2x+1)(x1)2(x21)2=4(2x1)(x2+2x+1)(2x+1)(x22x+1)=4(x42x2+1)2x3+4x2+2xx22x12x3+4x22xx2+2x1=4x48x2+43x21+3x21=4x48x2+46x22=4x48x2+44x414x2+6=02x47x2+3=02x46x2x2+3=02x2(x23)(x23)(x23)(2x21)x=±3x=±12=±22x{3,3,22,22}
Answered by Rasheed.Sindhi last updated on 23/Mar/25
x^2 (x+1)^2 +x^2 (x−1)^2 =6(x^2 −1)^2   x^2 {(x^2 +2x+1)+(x^2 −2x+1)}=6(x^4 −2x^2 +1)  x^2 (2x^2 +2)=6x^4 −12x^2 +6  2x^4 +2x^2 =6x^4 −12x^2 +6  4x^4 −14x^2 +6=0  2x^4 −7x^2 +3=0  2x^4 −6x^2 −x^2 +3=0  2x^2 (x^2 −3)−(x^2 −3)=0  (x^2 −3)(2x^2 −1)=0  x=±(√3) ∨ x=±((√2)/2)
x2(x+1)2+x2(x1)2=6(x21)2x2{(x2+2x+1)+(x22x+1)}=6(x42x2+1)x2(2x2+2)=6x412x2+62x4+2x2=6x412x2+64x414x2+6=02x47x2+3=02x46x2x2+3=02x2(x23)(x23)=0(x23)(2x21)=0x=±3x=±22

Leave a Reply

Your email address will not be published. Required fields are marked *